Posttransplant Immune Activation: Innocent Bystander or Insidious Culprit of Posttransplant Accelerated Atherosclerosis. Issue 9 (September 2017) - Ducloux, Didier; Bamoulid, Jamal; Crepin, Thomas; Rebibou, Jean-Michel; Courivaud, Cecile; Saas, Philippe
Cardiovascular disease is a major cause of morbidity, disability, and mortality in kidney transplant patients. Cumulative reports indicate that the excessive risk of cardiovascular events is not entirely explained by the increased prevalence of traditional cardiovascular risk factors. Atherosclerosis is a chronic inflammatory disease, and it has been postulated that posttransplant immune disturbances may explain the gap between the predicted and observed risks of cardiovascular events. Although concordant data suggest that innate immunity contributes to the posttransplant accelerated atherosclerosis, only few arguments plead for a role of adaptive immunity. We report and discuss here consistent data demonstrating that CD8 + T cell activation is a frequent posttransplant immune feature that may have pro-atherogenic effects. Expansion of exhausted/activated CD8 + T cells in kidney transplant recipients is stimulated by several factors including cytomegalovirus infections, lymphodepletive therapy (e.g., antithymocyte globulins), chronic allogeneic stimulation, and a past history of renal insufficiency. This is observed in the setting of decreased thymic activity, a process also found in elderly individuals and reflecting accelerated immune senescence.